Anmeldelse af KIT’ s jubilæumsskrift: FOOLS25 - C. Rohweder, Nanna (Peripeti, 2024)
The issue has been reconstructed from a scanned version of a printed issue, which might result in minor flaws in the text. This is also the cause of the odd page breaks.